Physicochemical Analysis of Sulfide Groundwater in the Ejido Puente Negro in Coahuila, Mexico, Community Diagnosis and Proposal for Sulfide Desorption - Martínez-Carrillo, Diego; Guerrero-Bermea, Cynthia; Alcalá-González, Guadalupe Esmeralda; Alcalá-González, Rubí; Martínez-Tovar, Hilda Cristina; Alcalá-González, Perla Mayara; Hernández-Rodríguez, José Caín; Enciso-Cárdenas , Juan Josué; Ávila-Orta, Carlos Alberto (REVISTA TERRA LATINOAMERICANA, 2025)
The Ejido Puente Negro is characterized by the economic activities of farming and agriculture, despite having extensive periods of drought. Access to groundwater through dug wells is one of the main alternatives to meet the living needs of its inhabitants. However, poor practices have resulted in groundwater degradation, compromising phreatic mantles. The generation of treatment methods results in a good option to supply the population and ensure its quality. However, it is essential that residents are informed and have suf ficient knowledge to implement these practices. The present work shows a physicochemical study of groundwater from dif ferent wells located in the Ejido. A kinetic analysis of the desorption of sulfides was also carried out, concluding that their natural desorption is suf ficient to reduce more than 70% of their concentration in a period of 6 days. Additionally, the geology of the area is assessed in search of possible influence on groundwater contamination. Finally, a social study is presented about contaminated groundwater, the health implications involved in its consumption, and the understanding of purification and reuse processes.